A retrospective cohort study to evaluate the development of comorbidities, including psychiatric comorbidities, among a pediatric psoriasis population. Issue 3 (21st February 2019) - Paller, Amy S.; Schenfeld, Jennifer; Accortt, Neil A.; Kricorian, Gregory
Abstract: Background/Objective: Compared with the adult psoriasis population, knowledge about the incidence of comorbidities in the pediatric psoriasis population is limited. The objective of this study was to assess the prevalence and incidence of comorbidities, including psychiatric comorbidities, in patients with pediatric psoriasis. Methods: In this claims‐based, retrospective cohort study, patients with pediatric psoriasis were matched 1:3 with a nonpsoriasis cohort based on age, sex, and index date (the earliest of inpatient claims or the latter of two outpatient claims). Results: Obesity, serious infection, and juvenile idiopathic arthropathy had higher prevalence and incidence rates in the psoriasis cohort than the nonpsoriasis cohort. Psychiatric comorbidities were also more common in the psoriasis cohort than the nonpsoriasis cohort, as were ulcerative colitis and Crohn disease. Stratifying the psoriasis cohort by disease severity—mild and moderate‐to‐severe—found no differences in incidence rates of comorbidities between the two subsets. Conclusion: The incidence rates of many comorbid conditions were higher for patients with pediatric psoriasis compared with patients without pediatric psoriasis, and similar between patients with moderate‐to‐severe and mild pediatric psoriasis.